The Role of Professionalism of Islamic Religious Education Teachers in Building a Religious School Environment at Integrated Islamic Elementary Schools - Zuhri; Nasution Nasution; Amini; Taubatul Adzkiya; Farah Damia Mohd Nasir (Universitas Pendidikan Ganesha, 2026)
The problem in this study departs from the suboptimal role of Islamic Religious Education (PAI) teachers in building a religious school environment and supporting the development of students with noble character. This study aims to analyze the role of PAI teachers' professionalism, which includes pedagogic competence, moral integrity, and spiritual leadership in shaping a religious school culture. This type of research is qualitative, using a case study design that involves eight research subjects, including PAI teachers, principals, and students. Data was collected through in-depth interviews, participatory observations, and documentation, then analyzed using thematic analysis, which included data reduction, data presentation, and conclusion. The results of the study show that the professionalism of PAI teachers has an essential role in fostering religious culture through example, worship habits, and synergy with parents and the school community. Teachers not only play the role of conveying material, but also as moral and spiritual role models who consistently instill Islamic values in students' daily lives. The conclusion of this study confirms that teacher professionalism, combined with ethical and spiritual dimensions, can form a sustainable model of religious character education. Implicitly, the results of this study highlight the importance of professional teacher training based on spiritual values, the strengthening of school and family collaboration, and Islamic education policies that emphasize integrating faith, ethics, and social responsibility into school learning practices.